Assessing the effect of seasonal agriculture on the condition and winter survival of a migratory songbird in Mexico. Issue 4 (20th March 2019) - Valdez‐Juarez, Simon O.; Krebs, Elizabeth A.; Drake, Anna E.; Green, David J.
Abstract : Migratory birds can spend 8 months of the year on their wintering grounds and the conversion of natural habitats to agriculture in Latin America has been implicated in population declines of several Neotropical migrants. Despite this, few studies have directly assessed the value of agricultural habitat for wintering migrants. We compared the condition and survival of Yellow Warblers ( Setophaga petechia ) occupying natural (riparian forest, scrub‐mangrove) and agricultural habitat (annually cropped sorghum, corn, and chili‐peppers separated by hedgerow) in western Mexico. We assessed condition with five metrics (daily and seasonal changes in size‐adjusted body mass, leukocyte profiles, rectrix regrowth rate, rectrix quality, and dates of departure on spring migration). We used Cormack–Jolly–Seber models fitted to mark‐resighting data collected over 4 years (2012–2015) to estimate January–May monthly survival rates. We found that birds occupying agricultural habitat and riparian forest had higher monthly apparent survival between January and May than birds in scrub‐mangrove. Birds in agricultural habitat also grew higher quality feathers (i.e., rectrices with a higher barbule density) than those in natural habitat. In contrast, birds in agricultural habitat were lighter than those in riparian habitat. We found no detectable effect of winter habitat use on daily or season changes in size‐adjusted mass and H/L ratios, although the effect of winter habitat use on departure rates differed for males and females. Our results demonstrate that agricultural habitat may provide suitable winter habitat for a long‐distance migrant and suggest that feather quality can be an indicator of winter habitat quality.